Optimasi Carnauba Wax dan Paraffin Wax Pada Lipstik Ekstrak Umbi Bit (Beta vulgaris) Dengan Metode Simplex Lattice Design - Sumule, Arsiaty (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Decorative preparations, such as lipstick, are women's dreams. The dyes used in lipstick formulas must comply with safety standards because this cosmetic product is applied to the mouth area, which can be swallowed through food, drinks, or saliva. Therefore, natural dyes appear to be a safe alternative with minimal side effects. The abundance of beetroot in Indonesia can make it a potential natural dye in cosmetic formulas. The physical form of lipstick also needs to be considered because it plays an important role in the characteristics and stability of the preparation. Therefore, a wax base is needed in the lipstick formula. Formula optimization can determine the optimal ingredient ratio without trial and error, thus saving time, costs, and materials. The purpose of this study was to determine the effect of the combination of carnauba wax and paraffin wax on the physical properties of beetroot extract lipstick and determine the optimum beetroot extract lipstick formula. This type of research is experimental by making eight lipstick formulas with variations of carnauba wax and paraffin wax and testing their physical properties, such as organoleptic, pH value, adhesion power, and melting point. The results were analyzed using Design Expert 11.1.2.0 software with the simplex lattice design method to obtain the optimum formula. The results showed the optimum formula of beetroot extract lipstick with a combination of 10% carnauba wax and 10% paraffin wax so that the pH value was 6.509, the adhesive power was 98.667 seconds, and the melting point was 67.931oC. The combination of carnauba wax and paraffin wax affects physical properties, such as pH value, adhesive power, and melting point in beetroot extract lipstick preparations.